Factors affecting seminal quality in bulls (2009)
Semen quality of bulls can be affected by multiple causes, both infectious and non infectious. Proper understanding of these causes is imperative, either to take the necessary correctives to treat the bull or to discard it from the productive system. It is important not to forget that the physical presence of the bull can be from a germoplasm bank (frozen semen) which can have quality problems not related to the cryopreservation procedure but to infectious or not infectious factors before freezing. Seminal quality problems will be reflected on different reproductive parameters of the productive system and these will be highly relevant when estimating earnings and losses of the productive system, both for beef or milk production.